Adult learning and education in the Mediterranean - a view from southern Europe - Mayo, Peter (International Review of Education, 2024)
This article examines the key role that adult learning and education (ALE) has played and continues to play in addressing the challenges faced by critical engagement with identities and crossing borders in the Mediterranean region. Despite the great cultural, economic and educational diversities characterising the region, the author explores whether a distinctive and recurring pattern of ALE exists or is likely to emerge. His analysis highlights historical and contemporary landmarks (features) of ALE in the region which exist alongside others from "mainstream" European education put forward by such funding agencies as the European Union (EU). While the landmarks are distinctive, they do offer recurring patterns which are characteristic of social-purpose ALE provision in the region. Much can be drawn from ALE in the Mediterranean, together with useful insights from other parts of the world, to foster intercultural engagement in response to mass migration in the region.
Keywords: Adult Literacy; Critical Literacy; Rhythms of Life; Adult Learning